A randomized, sham-controlled trial of high-definition transcranial direct current stimulation on the right orbital frontal cortex in children and adolescents with attention-deficit hyperactivity disorder - Wang, Yi-chao; Liu, Jun; Wu, Yan-chun; Wei, Yan; Xie, Hong-jing; Zhang, Tao; Zhang, Zhen (Frontiers in Psychiatry, 2023)
Objective：This study aims at finding out the clinical and cognitive effect of High-Definition transcranial direct current stimulation (HD-tDCS) on the right orbital frontal cortex (OFC) in the treatment of attention deficit hyperactivity disorder (ADHD). Methods：Fifty-six ADHD patients were recruited as subjects and completely, randomly divided into the HD-tDCS group and Sham group. A 1.0 mA anode current was applied to the right OFC. The HD-tDCS group received real stimulation, while the Sham group received sham stimulation in 10 sessions of treatment. ADHD symptom assessment (SNAP-IV Rating Scale and PSQ questionnaire) was carried out before treatment, after the 5th and the 10th stimulus, and at the 6th week after the end of all stimulation, while cognitive effect was assessed by Integrated Visual and Auditory Continuous Performance Test (IVA-CPT), Stroop Color and Word Test(Stroop), and Tower of Hanoi (TOH). Repeated-measure ANOVA was used to find out the results of both groups before and after treatment. Results：Forty-seven of the patients completed all sessions and evaluations. SNAP-IV, PSQ score and the visual correct response number of IVA-CPT, the mean visual and auditory reaction time of IVA-CPT, the Interference RT of Color and Word of Stroop, the number of completed steps of TOH did not change with intervention time before and after treatment (P>0.0031). However, in the visual and audiovisual combination comission errors of IVA-CPT, TOH completion time of the two groups, the results showed that the HD-tDCS group was significantly decreased after the 5th intervention, the 10th intervention and the 6th week of intervention follow-up compared with Sham group (P<0.0031). Conclusion：This study draws cautious conclusions that HD-tDCS does not significantly allivate the overall symptoms of ADHD patients, but leads to significant improvements of cognitive measures of attention maintaining. This study also fills in the gap of researches on HD-tDCS stimulating right OFC.